Additions to Karst Fungi 5: Sardiniella guizhouensis sp. nov. (Botryosphaeriaceae) associated with woody hosts in Guizhou province, China - Chen, Ya-Ya; Dissanayake, Asha J.; Liu, Jian-Kui (Phytotaxa, 2021)
During an investigation of ascomycetous fungi in Karst formations of the Asian region, three interesting taxa were found on dead aerial stems of woody hosts in Guizhou province, China. Their morphology assigned them as typical botryosphaeriaceous species. Phylogenetic analyses based on a combined DNA dataset of large subunit (LSU), internal transcribed spacer (ITS) and part of the translation elongation factor 1-α (tef1) gene confirmed their placement within Botryosphaeriaceae. In the phylogenetic tree, the three isolates formed a well-supported monotypic clade as a distinct lineage within the genus Sardiniella. Therefore, a new species Sardiniella guizhouensis sp. nov. is introduced to accommodate these taxa and detailed, illustrated descriptions of the asexual and sexual morphs are provided. This study reveals the first sexual morph of Sardiniella, which it is characterized by 2–4(–6)-spored asci with hyaline to brown, aseptate to 1-septate, ovate to subclavate ascospores.